Tingkat Pengangguran Berdasarkan Jumlah Penduduk, Pendapatan Perkapita, dan Investasi Asing di Indonesia Tahun 1996-2020 - Nova Elia; Marselina Marselina (Studi Ekonomi dan Kebijakan Publik, 2023)
Purpose: This study aims to analyze and prove the effect of population, per capita income, and foreign investment on the open unemployment rate in Indonesia, including population, per capita income, and foreign investment.  Methodology: The method used in this research is multiple linear regression analysis with the least squares or ordinary least square calculation model, namely by minimizing the sum of the squares of the regression error or error. Results: The results of this study are that the number of people has a statistically significant positive effect; GDP Per Capita has a statistically significant negative effect; and foreign investment has a statistically significant negative effect on the Open Unemployment Rate. Conclusion: All independent variables have a significant effect on the open unemployment rate in Indonesia.